Thermal inactivation of Escherichia coli (ATCC 25922) in tilapia (Oreochromis niloticus) meat homogenate - Sevilla, Kristine Pajarillo; Gabriel, Alonzo Alulod (2006)
ABSTRACT This study established the thermal resistance characteristics, D- and Z-values, of Escherichia coli ATCC 25922 in a tilapia meat homogenate. Known number of E. coli were inoculated in irradiated tilapia meat prior to heat treatment at 65, 70 and 75°C. Survivor cells were enumerated by surface plating onto pre-solidified Eosin Methylene Blue Agar. The D-values calculated from the E. coli survivor curves ranged from 0.50 to 1.13 min while the Z-value calculated from the thermal death time curve was 28.47°C. Validation of the results by establishing the thermal resistance of other E. coli reference strains in tilapia meat homogenate was recommended
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tilapia; Fish -- Microbiology. -- Philippines